Effects of Tilmicosin Treatment on the Nasopharyngeal Microbiota of Feedlot Cattle With Respiratory Disease During the First Week of Clinical Recovery - Zeineldin, Mohamed; Lowe, James; Aldridge, Brian (Frontiers in Veterinary Science, 2020)
While the nasopharyngeal (NP) microbiota is believed to be a key player in bovine respiratory health, there is limited published information about the change of NP microbiota associated with clinical recovery from bovine respiratory disease (BRD). The objective of this study was to evaluate the effect of tilmicosin treatment on the NP microbiota composition and diversity of BRD-affected calves during the first week of clinical recovery. Deep NP swabs were collected from diseased calves at the initial diagnosis of BRD, and again 7 days after the administration of a single dose of tilmicosin. As an experimental control, samples were collected from clinically healthy, pen-matched calves at the time of initial BRD diagnosis. In general, the NP microbiota from the control calves were more diverse than the NP microbiota from tilmicosin treated and BRD-affected calves. Principle coordinate analysis (PCOA) of Bray-Curtis and Jaccard dissimilarity also revealed that the overall composition of NP microbial communities in tilmicosin-treated calves closely resembled that of BRD-affected calves but differed significantly from pen-matched healthy calves. Overall, it appeared that there were only minor changes in NP microbial communities following tilmicosin treatment and, during the early phase of clinical recovery the NP microbiota in treated animals was disparate from that observed in healthy control calves. Understanding the potential impact of this prolonged recovery in mucosal microbiota would be important in optimizing the use of antimicrobials in health management programs in the feedlot industry. Keywords: Respiratory disease, Feedlot, Microbiota, Tilimicosin, 16S rRNA gene.